2017
DOI: 10.1017/s1368980017002348
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the dinner table: who’s having breakfast, lunch and dinner family meals and which meals are associated with better diet quality and BMI in pre-school children?

Abstract: Objective Having frequent family dinners is associated with better diet quality in children however, it is unknown whether the frequency of certain family meal types (i.e., dinner) are more strongly associated with better child weight and diet quality compared to other meal types (i.e., breakfast, lunch). Thus, the current study examined the frequency of eating breakfast, lunch, or dinner family meals and associations with preschool child overall diet quality (HEI-2010) and body mass index (BMI) percentile. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
28
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 41 publications
4
28
0
1
Order By: Relevance
“…Although prior research has identified some important factors within the home environment that are protective for childhood obesity risk, there are important limitations and unanswered questions that still exist. First, research has shown that frequent family meals, 1619 non-controlling parent feeding practices, 20,21 healthful food availability/accessibility in the home, 20 and authoritative parenting style 2125 are associated with more healthful dietary intake (e.g., fruit/vegetables), 2628 less consumption of sugar-sweetened drinks and fast food, 29 and fewer weight control behaviors 3033 in youth. However, many of the above findings have been inconsistent across studies with minority and low-income families.…”
Section: Introductionmentioning
confidence: 99%
“…Although prior research has identified some important factors within the home environment that are protective for childhood obesity risk, there are important limitations and unanswered questions that still exist. First, research has shown that frequent family meals, 1619 non-controlling parent feeding practices, 20,21 healthful food availability/accessibility in the home, 20 and authoritative parenting style 2125 are associated with more healthful dietary intake (e.g., fruit/vegetables), 2628 less consumption of sugar-sweetened drinks and fast food, 29 and fewer weight control behaviors 3033 in youth. However, many of the above findings have been inconsistent across studies with minority and low-income families.…”
Section: Introductionmentioning
confidence: 99%
“…Based on prior EAT study research and related studies addressing family meals, the survey included measures of family meal frequency, mealtime importance, and barriers to family meals. 23,[29][30][31][32][33] In addition, as community-based initiatives have raised concerns about "overscheduled kids," measures were added to assess whether parents with children aged 2 to 18 years perceived youth activities to interfere with family meals. 34 Focus groups with a separate community-based sample of 35 participants (aged 25 to 35 years), including parents and nonparents, were used to pretest a draft survey.…”
Section: Survey Developmentmentioning
confidence: 99%
“…15,16 However, little is known about specific meal characteristics (e.g., who prepared the meal, who is present at the meal, emotional atmosphere of the meal, what was served at the meal) [17][18][19] and whether these characteristics differ by family meal types including, breakfast, lunch, or dinner family meals. 20,21 In addition, it is unclear which meal characteristics are associated with family meal frequency. Furthermore, prior research has not included real-time measures of meal characteristics, which makes it difficult to determine whether these family meal characteristics vary across time and context.…”
Section: Introductionmentioning
confidence: 99%
“…It is important to identify characteristics of breakfast, lunch, and dinner family meals because prior research has suggested that family meals eaten at any time may convey similar health benefits. 20,24 Additionally, the majority of previous research has utilized self-report surveys and questionnaires to evaluate meal characteristics, which tend to be static measures. 2,3,[5][6][7][8][9]12 The current study utilizes Ecological Momentary Assessment (EMA), which uses real-time data collection methods, 25,26 to examine meal characteristics.…”
Section: Introductionmentioning
confidence: 99%